Surgical Technique, Tips, and Tricks: Medial Implantable Shock Absorber for Medial Compartment Knee Osteoarthritis - Andrew S. Bi MD; Wendell W. Cole MD; Dylan Lowe MD; Alexander Golant MD; Laith M. Jazrawi MD (Video Journal of Sports Medicine)
Background: Isolated medial compartment knee osteoarthritis (OA) presents a challenging problem to treat for knee surgeons, with a multitude of options from conservative management, including injections and unloader braces, meniscal procedures, osteotomies, and unicompartmental knee arthroplasty (UKA). A new medial implantable shock absorber (MISHA) allows for offloading 142 N of the medial compartment during stance phase of gait. Indications: US Food and Drug Administration approval was obtained on April 10, 2023, with the following indications: isolated medial knee OA (Kellgren-Lawrence grades I-IV) that failed 6 months of conservative management, ages 25 to 65 years, body mass index <35 or body weight <300 lbs, <15° of varus, no flexion contracture >10°, and no significant medial osteophytes or medial meniscal extrusion. Technique Description: A longitudinal medial knee incision is made 1 cm proximal to the medial epicondyle to the pes insertion, around 3 cm medial to the tibial tubercle, exposing the superficial medial collateral ligament, and medial joint line. The establishment of the femoral anisometric point is critical to provide a 4-mm posterior condylar offset in 90° of flexion compared to full extension. A trial implant can be placed to confirm appropriate anisometry, implant loading in extension, and relaxation in flexion. The final implant is placed and the titanium femoral and tibial baseplates are fixed with 3 unicortical titanium locking screws each. Results: Expected results per recommended postoperative protocol are immediate weightbearing without range of motion restrictions. From author experience, patients typically feel improvement and return to sport more rapidly than with anterior cruciate ligament reconstructions. Recovery and return to work are faster than osteotomies or UKAs based on comparative short-term studies. While long-term results are lacking given the novelty of the procedure, prospective studies have demonstrated 100% arthroplasty-free survival at 2 years and 85% survival at 5 years. Discussion/Conclusion: The MISHA is a viable option for isolated medial compartment knee OA that provides a joint-preserving alternative to arthroplasty and a less morbid alternative to osteotomy. This treatment can be technically difficult to perform, but several pearls and techniques can offer a reproducible, minimally invasive surgery and good functional results. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.